Direct observation of the photoinduced electron transfer processes of bis(4-arylphenylamino benzo)-ortho-carborane using transient absorption spectroscopic measurements. Issue 36 (11th September 2017) - Son, Mi Rang; Cho, Yang-Jin; Kim, So-Yeon; Son, Ho-Jin; Cho, Dae Won; Kang, Sang Ook
Abstract : The characteristic Cb˙ − and Ar˙ + species of ortho -carborane triads generated by the photoinduced electron transfer are investigated by transient absorption measurement. Abstract : The intramolecular photoinduced electron transfer (PET) processes of three bis(4-arylphenylamino benzo)- ortho -carboranes (ArCbAr, Ar = phenyl (Ph), naphthyl (Np) and pyrenyl (Py)) triads were investigated in CH2 Cl2 and n -hexane using the femtosecond time-resolved transient absorption (TA) spectroscopic technique. In CH2 Cl2, the transient S1 –S n absorption band of 1 ArCbAr* was observed at short delay times. Concomitant with the decay of 1 ArCbAr*, the TA bands for cation radical species were detected at around 700 nm for Ph˙ +, 650 nm for Np˙ +, and 580 nm Py˙ + . At the same time, the TA band of the carborane anion radical (Cb˙ − ) was observed at around 430 nm. This implies that the intramolecular PET process occurs from the 1 ArCbAr* state. The TA bands of the cationic and anionic radical species can be assigned by comparison to the absorption spectra of an electrochemically generated radical species. The PET process also occurs in n -hexane, as demonstrated by the monitoring of radical species in the TA spectra. In n -hexane, the TA band for Ar˙ + interfered with the aggregation induced emission (AIE) at early delay times. The long lived Ar˙ + species can be observed in the TA spectra at long delay times after fading of the AIE. The PET is exergonic in both solvents, as shown by the negative Gibbs energies (Δ G ) for the PET processes.